Odpowiedzi

Najlepsza Odpowiedź!
2010-01-25T19:33:17+01:00
A:3x²-xy B: -2y C: 3x
a) (A×B)×C = [(3x²-xy) × (-2y)] × 3x = (-6x²y+2xy²) × 3x = -18x³y+6x²y²

b) A×(B×C) = (3x²-xy) × [(-2y) × 3x] = (3x²-xy) × (-6xy) = -18x³y+6x²y²

c) (A+B)×C = [(3x²-xy)+(-2y)] × 3x = (3x²-xy-2y) × 3x = 9x³-3x²y-6xy

d) A×C+B×C = (3x²-xy) × 3x + (-2y) × 3x = 9x³-3x²y-6xy
2010-01-25T19:35:31+01:00
A:3x²-xy B: -2y C: 3x

(A×B)×C
[(3x²-xy)(-2y)]3x= [-6x²y+2xy²]3x=-18x³y+6x²y²


A×(B×C)
3x²-xy(-2y*3x)=3x²-xy * -6xy= -18x³ + 6x²y²

(A+B)×C
[3x²-xy + (-2y)]3x=9x³ - 3x²y -6xy

A×C+B×C
(3x²-xy)*3x + (-2y)*3x = 9x³-3x²y - 6xy

.. nie jestem pewna czy dobrze..
sprawdz..^^